2017
DOI: 10.1136/ejhpharm-2017-001258
|View full text |Cite
|
Sign up to set email alerts
|

Adherence and preference of intravenous zoledronic acid for osteoporosis versus other bisphosphonates

Abstract: ObjectiveTo evaluate adherence as well as patient preference and satisfaction of once-yearly intravenous zoledronic acid versus other bisphosphonates treatments.MethodsIn accordance with the PRISMA guidelines, a systematic literature search was conducted in PubMed, Cochrane Library and EMBASE databases, over the date range of 2000–2016. Following the PICO (Population, Interventions, Comparator, Outcomes) elements, eligibility criteria included: (1) participants: adults over 18 with osteoporosis and adults who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…Bisphosphonate therapy for osteoporosis also offer LA oral and injectable therapy to overcome challenges to daily oral adherence. 4 Related to both adherence and persistence on therapy, weekly oral therapy and less frequent injectable therapy perform better than daily oral therapy. 5 - 8 Adherence to once yearly intravenous zolendronic acid, measured as proportion of days covered (PDC), was higher compared to quarterly intravenous ibandronate (82% vs 60%, p < 0.0001).…”
mentioning
confidence: 99%
“…Bisphosphonate therapy for osteoporosis also offer LA oral and injectable therapy to overcome challenges to daily oral adherence. 4 Related to both adherence and persistence on therapy, weekly oral therapy and less frequent injectable therapy perform better than daily oral therapy. 5 - 8 Adherence to once yearly intravenous zolendronic acid, measured as proportion of days covered (PDC), was higher compared to quarterly intravenous ibandronate (82% vs 60%, p < 0.0001).…”
mentioning
confidence: 99%
“…Intravenous zoledronate was the predominant treatment in SIOUX (60%), followed by oral bisphosphonates (26%). In the literature, intravenous zoledronate persistence at 1 and 2 years was 66%‐70% and 25%, respectively 14‐16 (3‐year persistence is unknown 13 ). This is significantly better than persistence with oral medications: 14 a large systematic review of 89 studies found that >70% showed that 2‐year oral bisphosphonate persistence was <30% and only 21%‐40% of patients persisted with oral bisphosphonates at 3 years 8 .…”
Section: Discussionmentioning
confidence: 99%
“…This both reduces treatment rates and hampers medication persistence: 8‐12 for example, only 21%‐40% of patients persist with oral bisphosphonates at 3 years 8 . While 1‐year dose medications like intravenous zoledronate improve persistence, 13,14 1‐year persistence is still only 66%‐70% 14‐16 …”
Section: Introductionmentioning
confidence: 99%
“…It is an artificial compound, which can specifically inhibit osteoclast-mediated bone resorption, inhibit the activation of osteoclasts, and have a direct effect on the final formation and activation of osteoclasts to accelerate the apoptosis of such cells and increase BMD. 16,17 In addition, intravenous administration was used in the study, which greatly avoided the adverse reaction of digestive tract caused by oral administration of bisphosphonates and improved the compliance of patients.…”
Section: Discussionmentioning
confidence: 99%